2022
DOI: 10.1002/jcsm.12890
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, prevalence, and mortality of sarcopenia in dialysis patients: a systematic review and meta‐analysis

Abstract: There is no consensus on the prevalence of sarcopenia or its impact on mortality in end-stage renal disease patients undergoing dialysis. This review aimed to summarize the diagnostic criteria of sarcopenia and its prevalence and impact on the mortality of end-stage renal disease patients undergoing dialysis. Embase, MEDLINE, PubMed, and Cochrane Library were searched from inception to 8 May 2021 to retrieve eligible studies that assessed muscle mass by commonly used instruments, such as dual-energy X-ray abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 82 publications
8
97
1
Order By: Relevance
“…Such strategies have, however, been linked to further weakness, mobility limitations increasing the risk of future falls and, as was the case within our study, social isolation, and loneliness [ 44 ]. These issues may be particularly problematic in the HD population who already have a high burden of sarcopenia, frailty and treatment, and low levels of social participation [ 47 , 48 , 49 ]. Our findings indicate that more effective strategies for falls prevention in the HD population are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies have, however, been linked to further weakness, mobility limitations increasing the risk of future falls and, as was the case within our study, social isolation, and loneliness [ 44 ]. These issues may be particularly problematic in the HD population who already have a high burden of sarcopenia, frailty and treatment, and low levels of social participation [ 47 , 48 , 49 ]. Our findings indicate that more effective strategies for falls prevention in the HD population are urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of sarcopenia was 37.7%. A recent meta-analysis showed that the prevalence of sarcopenia in patients receiving PD was 4-48% 5 . Although the prevalence range is very wide due to the different criteria applied for sarcopenia and ethnicities, the prevalence of sarcopenia in our study is within the range reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using a nutritional risk index, higher scores indicating worse nutritional state were found to be associated with lower muscle mass, lower strength, and lower physical performance in haemodialysis patients [37]. Similar to the general population, sarcopaenia has been found to be associated with increased frailty and higher rates of mortality [38 ▪ ,39]. The prevalence of sarcopaenia in older haemodialysis patients was found to be between 37 and 40% [40].…”
Section: Sarcopaenia and Haemodialysismentioning
confidence: 95%